1980
DOI: 10.1080/03610738008258384
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of biological age

Abstract: One of the objectives of gerontological research is to achieve, reproducibly and at will, a verifiable discrepancy between the chronological and biological age of organisms. To accomplish this, the experimenter must be in a position to measure biological age independently. In theory, this can be done in the three ways: by actuarial analysis of large populations, assessment of overall morbidity, or observation of chronic degenerative changes that can be actually measured or graded according to a scale. Of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Many efforts have been made to define the best means of measurement of biomarkers of aging, but considerable disagreement exists concerning the logical strategy for criteria of selection as well as its concept (Adelman, 1987;Baker and Sprott, 1988;Ingram, 1988;Ludwig and Smoke, 1980;Masoro, 1988). Some problems are associated with crosssectional criteria of selection of biomarkers of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to define the best means of measurement of biomarkers of aging, but considerable disagreement exists concerning the logical strategy for criteria of selection as well as its concept (Adelman, 1987;Baker and Sprott, 1988;Ingram, 1988;Ludwig and Smoke, 1980;Masoro, 1988). Some problems are associated with crosssectional criteria of selection of biomarkers of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the simple, noninvasive and highly reliable nature of the selected biomarkers will make the BA prediction models practical diagnostic tools in assessing functional decline and vulnerability. Putative biomarkers of BA should represent function across several different physiological systems [28]. The selected biomarkers represent various functional capacities and physiological systems.…”
Section: Discussionmentioning
confidence: 99%
“…Driven by these goals, researchers in the 1970s and 1980s proposed a large number of candidate biomarkers of aging (Baker, 1975; Ludwig & Smoke, 1980; Ingram & Reynolds, 1986). Although these studies identified several putative biomarkers, many of the published multivariable composite scores were overfit—that is, overly tuned to a very specific dataset.…”
Section: Introductionmentioning
confidence: 99%